Pengobatan Menggunakan Jimat Dalam Perspektif Hadis - Adhariah, Aida; Amir, Sulaiman Muhammad; Halim, Abdul (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
This research aims to increase our understanding of the prohibition of treatment using amulets from the perspective of hadith and from the perspective of religious figures. Where this type of research is descriptive qualitative research with data analysis techniques. This method is also included in library research. Relevant data sources come from scientific works, namely journals, articles, news reports, magazines, books and so on. The results of this research are that the use of amulets, whether they come from the Qur'an or not, is clearly prohibited in the Hadith of the Prophet SAW, even the ulama also think so, and it is clear that the act is shirk which is mentioned in the Qur'an. Even though there are opinions from some scholars who say that amulets in Arabic are permissible with certain conditions, it is still best to avoid this because it can undermine the purity of the Qur‟an.